STRATEGIC BEHAVIOR MEASUREMENT IN MICRO AND SMALL BUSINESSES: AN ANALYSIS SUPPORTED BY THE MILES & SNOW TYPOLOGY (1978) - Cassol, Alessandra; Lorandi, Bruna; Carvalho, Antonio Oliveira de; Cintra, Renato Fabiano; Ribeiro, Ivano (Revista ADM.MADE, 2019)
<span style="font-size: 10.0pt; font-family: ";Calibri";,sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ";Times New Roman";; color: #212121; mso-ansi-language: EN-US; mso-fareast-language: EN-US;" lang="EN-US">The purpose of this article was to analyze the strategic behavior of micro and small-sized enterprises in accordance with the typology proposed by Miles and Snow (1978). The research used a quantitative approach through a survey. The analyzed data originates from 368 questionnaires applied in service-providers located in the city of Concórdia, Santa Catarina - Brazil. As a result, it was verified that the service-providers tend to use strategic behavior based on analytical placement. This suggests that the enterprises seek to maintain themselves in a stable market, but also seek for new products and markets. It was also observed that family enterprises and non-family enterprises have very similar strategic behaviors, indicating that the means of ownership does not condition strategic behavior, or at least does not differentiate them in a totally opposite polarization in their strategic behaviors. As a main contribution, this study demonstrates that the taken by the researched enterprises can be the result of dynamics of the environment and of the strategic mindset of its managers.